EXPANDING THE SOCIOLINGUISTIC SPACE FOR THE EMERGENCE OF HYBRID MOTHER TONGUES IN AFRICA: THE CASE OF KENYA (The University of Nairobi Journal of Language and Linguistics, 2023)
This paper examines the key factors to consider when selecting the language(s)that would be most appropriate as media of instruction in schools within a multicultural and multilingual setting - in this case Nairobi, the capital city of Kenya.The emergence and growth of urban codes in African urban spaces is a sociolinguistically significant phenomenon because it represents some recognition ofthese urban codes and places them into a „hybrid third space‟ where mixedlanguages and mixed identities are accommodated. Moreover, urban youth fromdifferent ethnic backgrounds can challenge the traditional linguistic and culturalidentities of earlier generations that tend to categorize communities into rigidethnic identities and cultural frameworks. The growth and spread of urban codesin urban settings even as mother tongue languages is a dynamic process thatcontinues to grow despite deliberate efforts by educationists, language policymakers and other „language gatekeepers‟ to demonize and discourage their use,supposedly because they are to blame for the poor performance of studentsduring national examinations, particularly those that test competence andperformance in English and Kiswahili – Kenya‟s official languages (the latterhaving the added accolade of being the national language). The argument in thispaper is that this blanket condemnation and prohibition of urban children andyouth to use familiar urban codes as their preferred forms of communication,which serves as a mother tongue for some, violates the linguistic and culturalrights of children, particularly in Nairobi.